A Palaeontological Geosite Example: Hasanaga Stream, Akcadag, Malatya - Kaygili, Sibel; Avsar, Niyazi; Aksoy, Ercan (Tmmob Jeoloji Muhendisleri Odasi, 2017)
Rock, mineral, fossil associations, structure, geological section, landforms or a part of land which they represent current or former geological process, event or a specialty is defined geosite. Some geologic units containing fossil associations and outcropping along Hasanaga Stream located in the northwest of Akcadag which is a settlement of Malatya city in Eastern Anatolia Region, is seen as a good example to this definition. The age of the geological units that outcrop along Hasanaga Stream ranges from Mesozoic to Quaternary. Diversity of Tertiary sedimentary units along Hasanaga Stream is represented by Korgantepe, Yenice and Asartepe members of Eocene Darende Formation, Oligocene Muratli Formation and Lower Miocene Alibonca Formation. The geological units constitute a regular sequence range from Lutetian to Oligocene in Hasanaga Stream. Their abundant larger benthic foraminifera such as Nummulites, Alveolina and Discocyclina are the subject of this study and they have been evaluated within the scope of geological heritage. Along the Hasanaga stream also, there are many caves having traces of life in some of them, on both sides of the valley, in different sizes. Diversity of larger benthic foraminifera and karstic formations increases the scientific importance of the district.
Keywords: Darende Formation; Geosite; Hasanaga Stream; arger benthic foraminifera; Malatya; Eastern Turkey